(untitled) (Research, Society and Development, 2024)
This study aimed to assess the agronomic efficiency of different cassava cultivars in sole cropping and intercropped with beans to enhance productivity and strengthen Family Farming in the Planalto Médio region of Rio Grande do Sul, Brazil. Conducted in randomized blocks with four replications, the experiment included treatments such as Vassourinha cassava in sole cropping (T1), RS-13 cassava in sole cropping (T2), Vassourinha intercropped with Fepagro Triunfo or Garapiá beans (T3-T4), RS-13 intercropped with Fepagro Triunfo or Garapiá beans (T5-T6), Vassourinha intercropped with two rows of Fepagro Triunfo or Garapiá beans (T7-T8), and RS-13 intercropped with two rows of Fepagro Triunfo or Garapiá beans (T9-T10). Agronomic performance and yield components were evaluated for cassava in sole cropping and for both crops in intercropping systems. The Scheffé test examined the effects of intercropping on cassava fresh root mass. Efficient land use (ELU) revealed higher fresh root mass production in sole-cropped cassava, while intercropping with single rows of beans showed greater productivity. RS-13 cassava excelled in production components, and Fepagro Triunfo beans demonstrated high productivity in an intercropping system with Vassourinha cassava. All intercropping systems exhibited high ELU, suggesting that the cassava/bean intercropping is an agronomically efficient system for the development and strengthening of Family Farming in the region.